2008
DOI: 10.1111/j.1442-2050.2008.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

ZNRD1 might mediate UV irradiation related DNA damage and repair in human esophageal cancer cells by regulation of ERCC1

Abstract: The downregulation of zinc ribbon domain-containing 1 (ZNRD1) protein was recently found to partially reverse the resistance of human leukemia cells toward chemical therapeutic drugs. Therefore, the ZNRD1 protein might be involved in the process of DNA damage and repair. To explore the possible protective effects of ZNRD1 on DNA damage induced by ultraviolet (UV)-C irradiation in human esophageal squamous cancer cell line EC109, we designed and transfected a expression vector into EC109 cells, and established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, reverse findings were reported in tumorigenesis after HBV persistent infection. Previous study revealed that up‐regulation of ZNRD1 may function to inhibit DNA damage and enhance the DNA repair capacity , which is a important barrier to liver carcinogenesis . Hong et al found that up‐regulation of ZNRD1 could significantly inhibit the growth of cells, reduce tumor microvessel densities and inhibit the vascular endothelial growth factor (VEGF) production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reverse findings were reported in tumorigenesis after HBV persistent infection. Previous study revealed that up‐regulation of ZNRD1 may function to inhibit DNA damage and enhance the DNA repair capacity , which is a important barrier to liver carcinogenesis . Hong et al found that up‐regulation of ZNRD1 could significantly inhibit the growth of cells, reduce tumor microvessel densities and inhibit the vascular endothelial growth factor (VEGF) production.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ZNRD1 also implicates in the occurrence and development of cancers. It was reported to play a role in the process of DNA damage and repair by regulating the expression of excision repair cross‐complementing one (ERCC1) , to suppress cell proliferation , and to mediate the expression of microRNAs in cancers (i.e., miR‐214 and miR‐296) . Coincidentally, miR‐214 down‐regulation could contribute to tumor angiogenesis during HCC development , and miR‐296 up‐regulation could suppress virus replication by targeting the viral genome .…”
Section: Introductionmentioning
confidence: 99%
“…In ZNRD1-AS1, several SNPs (nucleotide polymorphisms) is identified as expression quantitative trait loci (eQTLs) SNPs, which are connected with the expression of ZNRD1 [94,95] . ZNRD1 is involved in DNA damage and repair via regulating the expression of excision repair cross-complementing 1 (ERCC1) [96] , to restrain cell proliferation and to regulate the expression of miRNAs in cancers [97,98] . Furthermore, ZNRD1 eQTLs SNPs in lncRNA ZNRD1-AS1 have an increased risk for persistent HBV-carriers HCC but a protective influence against chronic HBV infection [93] .…”
Section: Highly Upregulated In Liver Cancermentioning
confidence: 99%